If it's not what You are looking for type in the equation solver your own equation and let us solve it.
v+3+v=-13
We move all terms to the left:
v+3+v-(-13)=0
We add all the numbers together, and all the variables
2v+16=0
We move all terms containing v to the left, all other terms to the right
2v=-16
v=-16/2
v=-8
| 13/7n=13/4 | | (4x-3)+(2x+1)=88 | | 2-5x+3=2 | | -6(a-3)=15 | | |4n-1|=6 | | 34+6m=6(m+5) | | 9x-24=6x+6 | | 2+4r=-14 | | 7(u+2)=5u+18 | | 28=y/4-12 | | -m-33=3(5m-1)+2 | | 5/7(14d+63)=10d+19 | | 19=13x=32 | | 4=4x-28+20 | | 62d+20d=400+20d | | 4.9x^2+14x-36=0 | | 2k+2=20 | | 6v+3(5v-4)=(2v+5) | | 3(5x+7)-3x-9=12x+12 | | -8x+20=36 | | -m-33=3(5m-)+2 | | 4x+4+4x+3+4x=4x+4x+5x+3 | | 1x+13.2=21.6 | | (4x^2+9x-20x-45)(x+5)=0 | | 7/x=11/7 | | 2u+17=39 | | -3(3-4v)+7v=124 | | 62+20d=400+20d | | 20-7+3x4=40 | | x+20+(x+20)-18+x=88 | | 5y^2+40y-45=0 | | 89x•666+09=693 |